Klassenklima und Rückmeldungen aus der Sicht von Kindern im dritten und vierten Grundschuljahr im Zusammenhang mit ihren Lernprozessen im Leseunterricht. Vortrag auf der 23. Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe „Lernprozessbegleitung und adaptive Lerngelegenheiten im Unterricht der Grundschule“ - Hellmich, Frank; Hoya, Fabian Karl

Rückmeldungen und Kompetenzerwerbsprozesse im Leseunterricht der Grundschule – Ergebnisse aus einer empirischen Untersuchung. Posterpräsentation auf dem 24. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft. Thema: "Traditionen und Zukünfte" - Hoya, Fabian Karl; Hellmich, Frank

Rückmeldungen im Leseunterricht der Grundschule aus der Sicht von Grundschülerinnen und -schülern in Abhängigkeit von Klassenklima und Lehrer-Schüler-Beziehung. Vortrag auf der 79. Tagung der Arbeitsgruppe Empirische Pädagogische Forschung (AEPF) - Hoya, Fabian Karl; Hellmich, Frank

`Opportunities to learn´ in der Ausbildung angehender Lehrerinnen und Lehrer für den inklusiven Unterricht in der Grundschule. 7. Bundestreffen der Zentren für Lehrerbildung. Thema: "Chancengleichheit durch Inklusion. Neue Professionalisierungsstrategien in der Lehrerbildung" - Hellmich, Frank

Individuelle Bedingungen für Einstellungen von Grundschullehrerinnen und -lehrern zur Inklusion in Unterricht und Schule. Vortrag auf der 79. Tagung der Arbeitsgruppe Empirische Pädagogische Forschung (AEPF) - Hellmich, Frank; Görel, Gamze

Über Kompetenzen und Verwirklichungschancen von Adressat/innen Sozialer Arbeit - Landhäußer, Sandra (Kompetenz, Performanz, soziale Teilhabe Sozialpädagogische Perspektiven auf ein bildungstheoretisches Konstrukt)
Der Band greift die skizzierten Anforderungen und Problemstellungen für Soziale Arbeit auf und nimmt – sowohl theoretisch geleitet als auch empirisch fundiert – disziplinäre Verortungen im Kontext des Kompetenzdiskurses vor. Folgende Fragen stehen dabei im Vordergrund: In welche übergreifenden Diskurse ist die Kompetenzdebatte einzuordnen? Welche Perspektiven eröffnet der Kompetenzbegriff für die Soziale Arbeit? Wie lässt sich sozialpädagogische Kompetenz angemessen beschreiben? Wie ist die Qualifizierung sozialpädagogischer Fachkräfte zu gestalten? Welche Kompetenzen bringen Adressaten in sozialpädagogische Interaktionsprozesse ein? Welche Chancen eröffnet der Kompetenzbegriff im Kontext einer befähigungsorientierten Sozialen Arbeit? Welche Ambivalenzen und Grenzen bestehen?
Keywords: Handlungskompetenz Performanz Soziale Teilhabe

Efficient nitrogen-doping and structural control of hierarchical carbons using unconventional precursors in the form of deep eutectic solvents - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Fierro, José Luís G.; Luisa Ferrer, M.; Monte, Francisco del (J. Mater. Chem. A)
Deep eutectic solvents formed with unconventional carbon precursors were used for the preparation of hierarchical carbon monoliths and proved effective for doping the resulting carbons with nitrogen.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Sulfur-Doped Carbons Prepared from Eutectic Mixtures Containing Hydroxymethylthiophene as Metal-Free Oxygen Reduction Catalysts - Lopez Salas, Nieves; del Monte, Francisco; Tamayo, Aitana; Fierro, José Luís G.; De Lacey, Antonio L.; Ferrer, M. Luisa; Gutiérrez, María C. (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Kottmann, Brigitte; Miller, Susanne (Individuelle Förderung und Lernen in der Gemeinschaft)

"Schule für alle" - ein Projekt zur Förderung fachlicher und überfachlicher Kompetenzen - Kottmann, Brigitte (Kompetenz - Bildung. Soziale, emotionale und kommunikative Kompetenzen von Kindern und Jugendlichen)

Lehrer in zwei Lehrämtern. Plädoyer für einen gestuften Lehramtsstudiengang - Kottmann, Brigitte (Schulverwaltung Nordrhein-Westfalen)

Optimizing spatial filters for the extraction of envelope-coupled neural oscillations - Dähne, S.; Nikulin, V. V.; Ramírez, D.; Schreier, P. J.; Müller, K.-R.; Haufe, S. (Proc. Int. Work. Pattern Recognition In Neuroimaging)
Amplitude-to-amplitude interactions between neural oscillations are of a special interest as they show how the strength of spatial synchronization in different neuronal populations relates to each other during a given task. While, previously, amplitude-to-amplitude correlations were studied primarily on the sensor level, we present a source separation approach using spatial filters which maximize the correlation between the envelopes of brain oscillations recorded with electro-/magnetencephalography (EEG/MEG) or intracranial multichannel recordings. Our approach, which is called canonical source power correlation analysis (cSPoC), is thereby capable of extracting genuine brain oscillations solely based on their assumed coupling behavior even when the signal-to-noise ratio of the signals is low.

Testing blind separability of complex Gaussian mixtures - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I. (Signal Process.)
The separation of a complex mixture based solely on second-order statistics can be achieved using the Strong Uncorrelating Transform (SUT) if and only if all sources have distinct circularity coefficients. However, in most problems we do not know the circularity coefficients, and they must be estimated from observed data. In this work, we propose a detector, based on the generalized likelihood ratio test (GLRT), to test the separability of a complex Gaussian mixture using the SUT. For the separable case (distinct circularity coefficients), the maximum likelihood (ML) estimates are straightforward. On the other hand, for the non-separable case (at least one circularity coefficient has multiplicity greater than one), the ML estimates are much more difficult to obtain. To set the threshold, we exploit Wilks’ theorem, which gives the asymptotic distribution of the GLRT under the null hypothesis. Finally, numerical simulations show the good performance of the proposed detector and the accuracy of Wilks’ approximation.

A Bayesian approach for adaptive multiantenna sensing in cognitive radio networks - Manco-Vásquez, J.; Lázaro-Gredilla, M.; Ramírez, D.; Vía, J.; Santamaría, I. (Signal Process.)

Optimum analog receive filters for detection and inference under a sampling rate constraint - Stein, Manuel; Lenz, Andreas; Mezghani, Amine; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Spatial Shaping and Precoding Design for Underlay MIMO Interference Channels - Lameiro, Christian; Utschick, Wolfgang; Santamaría, Ignacio (Proc. Int. ITG Work. Smart Antennas)

Information-preserving spatial filtering for direction-of-arrival estimation - Stein, Manuel; Castañeda, Mario; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Neue Anwendungsgebiete für Computer Assisted Surgery (CAS) - Schreier, Peter J. (ForschungsForum Paderborn)

Will the 1-bit GNSS receiver prevail? - Stein, Manuel; Nossek, Josef A. (Proc. of IEEE/ION PLANS 2014)

An asymptotic GLRT for the detection of cyclostationary signals - Ramírez, D.; Scharf, L. L.; Vía, J.; Santamaría, I.; Schreier, P. J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We derive the generalized likelihood ratio test (GLRT) for detecting cyclostationarity in scalar-valued time series. The main idea behind our approach is Gladyshev’s relationship, which states that when the scalar-valued cyclostationary sig- nal is blocked at the known cycle period it produces a vector- valued wide-sense stationary process. This result amounts to saying that the covariance matrix of the vector obtained by stacking all observations of the time series is block-Toeplitz if the signal is cyclostationary, and Toeplitz if the signal is wide- sense stationary. The derivation of the GLRT requires the maximum likelihood estimates of Toeplitz and block-Toeplitz matrices. This can be managed asymptotically (for large num- berofsamples)exploitingSzego ̈’stheoremanditsgeneraliza- tion for vector-valued processes. Simulation results show the good performance of the proposed GLRT.

Regularized successive interference cancellation (SIC) under mismatched modeling - Tong, Jun; Guo, Qinghua; Schreier, Peter J.; Xi, Jiangtao (Proc.\ IEEE Work.\ Stat.\ Signal Process.)
Successive interference cancellation (SIC) has been extensively applied to estimate transmit signals in communication systems. When the channel state information (CSI) and noise statistics are imperfectly estimated, the standard SIC estimators that ignore the model mismatch may perform poorly. This paper introduces regularized SIC estimation to provide robustness against the model mismatch. Suboptimal, low-complexity implementations using (sorted) QR decomposition and approximate choice of regularization parameters are also introduced. Simulation examples demonstrate that the regularized SIC estimators can significantly outperform the standard version.

Information-preserving transformations for signal parameter estimation - Stein, Manuel; Castañeda, Mario; Mezghani, Amine; Nossek, Josef A. (IEEE Signal Process.\ Lett.)

Real-time coherent detection of phase modulated ultrashort pulses after time-to-space conversion and spatial demultiplexing - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Time-multiplexed measurements of nonclassical light at telecom wavelengths - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Quantum teleportation from a telecom-wavelength photon to a solid-state quantum memory - Bussières, Félix; Clausen, Christoph; Tiranov, Alexey; Korzh, Boris; Verma, Varun B.; Nam, Sae Woo; Marsili, Francesco; Ferrier, Alban; Goldner, Philippe; Herrmann, Harald; Silberhorn, Christine; Sohler, Wolfgang; et al. (Nature Photonics)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

A source of polarization-entangled photon pairs interfacing quantum memories with telecom photons - Clausen, C; Bussières, F; Tiranov, A; Herrmann, Harald; Silberhorn, Christine; Sohler, W; Afzelius, M; Gisin, N (New Journal of Physics)
Keywords: General Physics and Astronomy

Generation of Nonclassical Biphoton States through Cascaded Quantum Walks on a Nonlinear Chip - Solntsev, Alexander S.; Setzpfandt, Frank; Clark, Alex S.; Wu, Che Wen; Collins, Matthew J.; Xiong, Chunle; Schreiber, Andreas; Katzschmann, Fabian; Eilenberger, Falk; Schiek, Roland; Sohler, Wolfgang; Mitchell, Arnan; et al. (Physical Review X)
Keywords: General Physics and Astronomy

Full-field reconstruction of ultrashort waveforms by time to space conversion interferogram analysis - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Tomography by Noise - Harder, G.; Mogilevtsev, D.; Korolkova, N.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Quantum Walks - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Silberhorn, Christine; Jex, Igor (Physical Review Letters)
Keywords: General Physics and Astronomy

Wandel von Autonomie und Kontrolle durch neue Mensch-Technik-Interaktionen. Grundsatzfragen autonomieorientierter Mensch-Technik-Verhältnisse - Gransche, Bruno; Shala, Erduana; Hubig, Christoph; Alpsancar, Suzana; Harrach, Sebastian
Wie lassen sich aktuelle und zukünftige Mensch-Technik-Verhältnisse autonomieorientiert erforschen, designen und (er)leben, sodass sie eine akzeptierbare und wünschbare Balance von Assistenz und Autonomie, von Komfort und Kontrolle ermöglichen? Wo immer Technik und Mensch zusammentreffen, entstehen und verschwinden Möglichkeiten, neue Handlungsoptionen und Schadenspotenziale. Dies ist für neue, komplexe soziotechnische Konstellationen angesichts von Nanotechnologie, kognitiven Robotern, allgegenwärtiger Vernetzung der kompletten Alltagswelt, Big Data-Anwendungen oder spielerischer Interaktionsgestaltung im Zuge von Gamification-Entwicklungen nur äußerst schwierig zu gestalten. Zentrale Konzepte, die diese Gestaltung orientieren können, wurden in diesem Band strukturiert. So können viele der disziplinübergreifenden Schwierigkeiten, die einem Großteil der Forschungsbemühungen des MTI-Bereiches gemeinsam sind, auch gemeinsam angegangen wer-den. Wie verteilen sich menschliche und technische Handlungsräume, Freiheitsgrade, Kontrollbereiche, Entscheidungsoptionen? Was heißt Autonomie, Kontrolle, Steuerung, Interaktion, Interface usw. im Sinne aktueller hybrider Systeme? Diese fundamentalen Querschnittfragen wurden mit Blick auf neue Formen der Mensch-Technik-Interaktion interdisziplinär nutzbar gemacht.

Configuration Determination of Transition Metal Complexes by Multiple Scattering EXAFS Analysis: A Case Study - Bauer, Matthias (Zeitschrift für Physikalische Chemie)
A multiple scattering extended X-ray absorption fine structure (EXAFS) analysis of Ti(acac) 2 Cl 2 is presented. With such an approach the configuration of the ligands in this complex can be identified due to the different multiple scattering events in the cis - and trans -configuration. A thorough evaluation of the effects of the different multiple scattering parameters (effective scattering path, scattering order, number of scattering atoms) in combination with the input structure is presented that reveals a complicated correlation between these parameters which could lead to wrong results with respect to the determined configuration. Finally, the optimal procedure for this particular purpose is defined and described.
Keywords: Physical and Theoretical Chemistry

Gels, xerogels and films of polynuclear iron(ii)–aminotriazole spin-crossover polymeric complexes - Sánchez-Ferrer, Antoni; Bräunlich, Irene; Ruokolainen, Janne; Bauer, Matthias; Schepper, Rahel; Smith, Paul; Caseri, Walter; Mezzenga, Raffaele (RSC Adv.)
Keywords: General Chemical Engineering; General Chemistry

BOX Ligands in Biomimetic Copper‐Mediated Dioxygen Activation: A Hemocyanin Model - Walli, Adam; Dechert, Sebastian; Bauer, Matthias; Demeshko, Serhiy; Meyer, Franc (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

A New Iron-Based Carbon Monoxide Oxidation Catalyst: Structure-Activity Correlation - Schoch, Roland; Huang, Heming; Schünemann, Volker; Bauer, Matthias (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Subcutaneous Administration of Drugs in Palliative Care: Results of a Systematic Observational Study. - Bartz, Lena; Klein, Carsten; Seifert, Andreas; Herget, Iris; Ostgathe, Christoph; Stiel, Stephanie (Journal of pain and symptom management)

The Three-Tiered Leuphana Model of Student Support. - Balsam, Rebecca; Newig, Jens; Seifert, Andreas (INFU Discussion Paper)

Feldstudie zur Entwicklung der Rechenfertigkeit von Erstklässlern. - Eilerts, Katja; Rinkens, Hans-Dieter; Seifert, Andreas (Beiträge zum Mathematikunterricht 2014)

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus - Steinhoff, Lena

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Müller, Wolfgang; Scheytt, J. Christoph (Proceedings of the Design and Verification Conference Europe (DVCON Europe))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.
Keywords: System Design; Verification

Problemorientierung in der polyvalenten Lehre: Forschendes Lernen vs. Praxisorientiertes Projektlernen. - Hellmann, Karina; Teigeler, Mareike; Seifert, Andreas (Greifswalder Beiträge zur Hochschullehre)

What we mean when we talk about freedom – The KOMFOR study: an analysis of students' choices of courses in interdisciplinary parts of the curriculum. - Seifert, Andreas; Strunz, Cathleen; Gunkel, Marjaana; Schütz, Julia (8th International Technology, Education and Development Conference (INTED))

Pädagogische Vorerfahrungen und motivationale Orientierungen als Prädiktoren der Kompetenzentwicklung im Bereich der Bildungwissenschaften. - Seifert, Andreas; Watson, Christina (AEPF-Tagung „Der Forschung / Der Lehre / Der Bildung”)

Nutzung von Lerngelegenheiten als Prädiktoren der Kompetenzentwicklung von Lehramtsstudierenden in den Bildungswissenschaften. - Seifert, Andreas; Watson, Christina (AEPF-Tagung „Der Forschung / Der Lehre / Der Bildung”)

Auf- und Ausbau Früher Hilfen in Zeiten knapper öffentlicher Kassen. Warum es sich lohnt, in Frühe Hilfen zu investieren - Wagenknecht, Inga; Meier-Gräwe, Uta (Zeitschrift für Paar-, Familien- und Sozialtherapie)

Vorerfahrungen und Selbstwirksamkeitsüberzeugungen als Prädiktoren für Einstellungen zum inklusiven Unterricht bei Lehrerinnen und Lehrern in der Grundschule. Vortrag auf der 23. Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe „Lernprozessbegleitung und adaptive Lerngelegenheiten im Unterricht der Grundschule“ - Görel, Gamze; Hellmich, Frank

Attributionen von Erfolgen und Misserfolgen bei Kindern im Leseunterricht der Grundschule im Zusammenhang mit Rückmeldungen ihrer Lehrkräfte. Vortrag auf der 23. Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe „Lernprozessbegleitung und adaptive Lerngelegenheiten im Unterricht der Grundschule“ - Ort, Margarita; Hellmich, Frank

Albrecht Greule, Jörg Meier und Arne Ziegler (Hgg.): Kanzleisprachenforschung. Ein internationales Handbuch. Unter Mitarbeit von Melanie Glantschnig, Jakob Reichsöllner und Elisabeth Scherr. Berlin/Boston: Walter de Gruyter, 2012 - Wallmeier, Nadine (Niederdeutsches Jahrbuch)

Interaction of a classical laser field with a model Rydberg atom in a mixed state prepared by entanglement with few-photon quantum light - Sharapova, Polina; Tikhonova, O V (Journal of Physics: Conference Series)
Keywords: General Physics and Astronomy